(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The crude methanol extract of leaves of Bauhinia acuminata and its Kupchan fractions were screened for antioxidant, cytotoxic and membrane stabilizing activities. Among all partitionates the aqueous soluble fraction of B. acuminata demonstrated the highest antioxidant activity with IC50 value of 7.22±0.200 ?g/ml. Moreover, the carbon tetrachloride soluble fraction showed significant cytotoxic activity having LC50 value of 12.13±0.215 ?g/ml. On the other hand, in hypotonic solution- and heat- induced conditions, the crude methanol extract inhibited haemolysis of human erythrocyte by 63.94±0.14% and 51.95±0.20%, respectively as compared to 81.97±0.77% and 42.11±0.39% demonstrated by the standard acetyl salicylic acid. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22324 Bangladesh Pharmaceutical Journal 17(1): 99-101, 2014